The Effect of the1Use of Audio-Visual Media on Learning Outcomes of Cultural Arts (Dance) Class XI Students at SMA Negeri 9 Padang - Muthia Annisa; Yuliasma (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study was to see and describe the influence of the use of audio-visual media on the academic achievement of grade 11 Cultural Arts (Dance) students of SMA Negeri 9 Padang. This type of research is experimental research. The population of this study is all students of SMA Negeri 9 Padang class XI science and social studies for the 2021/2022 academic year who are active in Semester 2 (up to) with a sample of 72 people from XI IPA3 and XI IPA5. The instrument in this study is in the form of an objective written test. Primary data and secondary data were used in this research material. Data collection techniques include tests (pre-test and post-test), observation and documentation. The material is analyzed using comparative test techniques to obtain average learning outcomes according to the T-test formula. The results of the study illustrate that during the same semester at SMA Negeri 9 Padang, the use of audiovisual media in dance education had a significant influence on the academic achievement of students in the field of cultural arts. It can be seen from hypothesis testing with a significance value of 0.000 and alpha (confidence level) of 0.05. From the average learning outcomes of the experimental class of 87.36 while the average learning outcomes of the reference class were 77.77. Then the difference between the experimental class and the control class is 9.95. The t-test value was calculated > ttabel (6.203>-1.799). So it can be concluded that the average difference between students who use audiovisual media and traditional media is 9.95 and the t test is (6,203>-1,799).